STUDI PERBANDINGAN TENTANG NILAI-NILAI KERJA BERDASARKAN PENDIDIKAN ORANG TUA DAN ASPIRASI KERJA SLTA NEGERI DI KODYA SURAKARTA - Daliman, Daliman (Universitas Muhammadiyah Surakarta, 1995)
The aim of this research is to know the differences of work values based on the differences of parentss levels of education, work aspirations, kind of school or school departement, and sex.The method employed to et the samples was